Wetlands for Sustainable Urban Environment in the New Township of Seri Iskandar - Sapari, Nasiman (2007)

(untitled)
Seri Iskandar is a new township with a large area of wetlands originating from natural swamps and mining lakes. This paper examines the potential of wetland areas to be developed into engineered wetlands for recreational purposes and flood control. One of the wetlands, a swampy area in the middle of the town, is an ideal location for a public recreational area. The size of the catchments is 124 ha and currently consists of about %5 developed areas and 95% forest and swamp. Rapid development of the town will eventually involve conversion of the forested part of the catchment for the extension government office complexes, industrial and commercial centers of the town. The environmental impact of the development among others will be on the hydrology and ecology of the area. Measurements and calculations were conducted on hydrological parameter in terms of the low-flow and high-flow characteristics, water retention capacities, and the aerial size of the water bodies. The peak flows for 100 years average recurrence interval (ARI) of the catchments is estimated to be about 7.3 m3/s. Engineered wetlands for the area that would allow a water fluctuation of 1 m height and 5 to 10 percent area under intermittent flooding could reduce up to 65% of the peak flow immediately downstream of the wetlands. As a result, the potential of flooding due to increase of runoff from the development of the town can be reduced. The wetlands will also function as habitats for flora and fauna essential for maintaining ecological balance in the area so as to prevent proliferation of certain species such as mosquitoes and other pests.